NON-REFLECTIVE INCIDENCE OF P-POLARIZED ELECTROMAGNETIC WAVES ON THE SOLID-STATE STRUCTURE "UNIAXIAL PLASMONIC METASURFACE — DIELECTRIC LAYER — METAL" - Beletskii, M. M.; Popovych, I. D. (Видавничий дім «Академперіодика», 2023)
Subject and Purpose. The solid-state structures involving metasurfaces can be used to effectively control some of the basic properties of electromagnetic waves, like amplitude, phase and polarization. The present work is aimed at analyzing the new effects that may appear during incidence of p-polarized electromagnetic waves upon a solid-state structure involving a uniaxial plasmonic metasurface, a dielectric interlayer, and a layer of metal.Methods and Methodology. The conditions suitable for identifying the effects that result from the reflection of a p-polarized electromagnetic wave incident upon a solid-state structure of the above described type have been sought for via numerical simulation. That has allowed finding the magnitudes of the essential parameters, such as angles of incidence and frequencies of the electromagnetic waves, as well as thicknesses of the dielectric interlayer, that could stipulate appearance of novel electromagnetic effects.Results. It has been shown that the solid-state structure involving a uniaxial plasmonic metasurface, a dielectric interlayer, and a layer of metal is capable, under certain conditions, to fully absorb an incident electromagnetic wave of p-polarization. Moreover, a new effect has been predicted, specifically that of full conversion of the incident p-polarized electromagnetic wave into a reflected wave of s-polarization. The necessary condition is that the plane of incidence of the electromagnetic wave were at an acute angle to the principal symmetry axis of the plasmonic metasurface.Conclusions. The solid-state structures of the type involving a uniaxial plasmonic metasurface, a dielectric interlayer, and a layer of metal are characterized by unique reflective properties. They are capable of fully absorbing, under certain conditions, the p-polarized electromagnetic waves incident upon them. Such structures can be used for creating optical and nanoelectronic devices of new types.Keywords: p-polarized electromagnetic waves, uniaxial plasmonic metasurface, polarization conversion, non-reflective incidenceManuscript submitted 27.06.2022Radio phys. radio astron. 2023, 28(2): 166-173REFERENCES1. Sakoda, K., 2019. Electromagnetic Metamaterials. Modern Insights into Macroscopic Electromagnetic Fields. Springer Singapore Publ. DOI: https://doi.org/10.1007/978-981-13-8649-72. Saleh, B.E.A., Teich, M.C., 2019. Fundamentals of Photonics. Wiley Publ. ISBN: 978-1-119-50687-4.3. Jiaming Hao, Yu Yuan, Lixin Ran, Tao Jiang, Jin Au Kong, Chan, C.T., and Lei Zhou, 2007. Manipulating Electromagnetic Wave Polarizations by Anisotropic Metamaterials. Phys. Rev. Lett., 99(6), 063908 (4 p.). DOI: https://doi.org/10.1103/PhysRevLett.99.0639084. Beletskii, N.N., Popovich, І.D., 2022. Influence of uniaxial plasmon metasurface on antireflection properties of dielectric layer. Radio Physics and Radio Astronomy, 27(1), pp. 75—80 (in Ukrainian). DOI: https://doi.org/10.15407/rpra27.01.0755. Kotov, O.V., Lozovik, Yu.E., 2019. Hyperbolic hybrid waves and optical topological transitions in few-layer anisotropic metasur- faces. Phys. Rev. B, 100(16), 165424(16 p.). DOI: https://doi.org/10.1103/PhysRevB.100.1654246. Yermakov, O.Y., Permyakov, D.V., Porubaev, F.V., Dmitriev, P.A., Samusev, A.K., Iorsh, I.V., Malureanu, R., Lavrinenko, A.V., & Bogdanov, A.A., 2018. Effective surface conductivity of optical hyperbolic metasurfaces: from far-field characterization to surface wave analysis. Sci. Rep., 8, 14135 (10 p.). DOI: https://doi.org/10.1038/s41598-018-32479-y7. Yermakov, O.Y., Ovcharenko, A.I., Song, M., Bogdanov, A.A., Iorsh, I.V., and Kivshar, Yu.S., 2015. Hybrid waves localized at hy- perbolic metasurfaces. Phys. Rev. B, 91(23), 235423 (23 p.). DOI: https://doi.org/10.1103/PhysRevB.91.235423